Polsko-litewskie dziedzictwo kulturowe – różnice w świadomości społecznej. Perspektywy zbliżenia dzięki wspólnym bohaterom narodowym na przykładzie Michała Kleofasa Ogińskiego - Gumper, Małgorzata (Studia Edukacyjne, 2021)
The uncomfortable situation of Poles in Lithuania is, among other things, the effect of Lithuanian historical education. Excerpts from the textbook on the history of Lithuania show diametrical differences in contemporary ideas about the past of both nations. Shared heroes are useful to overcome prejudices of the previous century (which affect the image of 1385-1795). One of them is Michał Kleofas Ogiński, Lithuanian nobleman, a political activist during the last years of the Polish-Lithuanian Commonwealth and two decades after its collapse. He has the rank of a great national hero in Lithuania and Belarus but is valued in Poland above all because of his piano compositions. The analysis of fragments of his work Memoirs about Poland and Poles helps us to regard a representative of the noble nation from a different perspective. It makes us aware of the cohesion of Polish and Lithuanian national identity at the turn of the 19th century, helps us to appreciate the heritage of the past and offers a chance to build positive relations between us. Rectifying a distorted vision of history is a prospect for a mature partnership now and in the future.